2011
DOI: 10.3109/00365513.2011.558108
|View full text |Cite
|
Sign up to set email alerts
|

β2-microglobulin, a novel biomarker of peripheral arterial disease, independently predicts aortic stiffness in these patients

Abstract: Arterial stiffness is a prominent feature of vascular ageing and strongly predicts cardiovascular and total mortality. The β2-microglobulin, (β2M) a newly identified biomarker of peripheral arterial disease (PAD), is related to renal insufficiency, inflammatory and neoplastic diseases, but may also play a role in vascular dysfunction. However, the relationship between arterial stiffness and β2M has not been previously studied in patients with atherosclerosis. In the present study we examined a possible associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 29 publications
3
22
1
Order By: Relevance
“…Plasma B2M levels and parameters of arterial stiffness such as aortic pulse wave velocity and augmentation index have been reported to be significantly increased in PAD patients [67]. Some studies have shown that combining these circulating markers of inflammation and atherosclerosis with clinical parameters may improve the identification of PAD patients [65,66,71].…”
Section: Potential Biomarkers For Padmentioning
confidence: 99%
“…Plasma B2M levels and parameters of arterial stiffness such as aortic pulse wave velocity and augmentation index have been reported to be significantly increased in PAD patients [67]. Some studies have shown that combining these circulating markers of inflammation and atherosclerosis with clinical parameters may improve the identification of PAD patients [65,66,71].…”
Section: Potential Biomarkers For Padmentioning
confidence: 99%
“…Several tools have been proven to accurately indicate peripheral atherosclerosis, beginning with markers of endothelial dysfunction expressed as flow-mediated dilatation (FMD), reactive-hyperemia index (RHI) or arterial pulse-waveform analysis (aPWA) indices and ending in clinically apparent lower limb atherosclerosis assessed by the ankle-brachial index (ABI) or toe-brachial index (TBI), finally proven by arterial angiography or arterial computed tomography [1][2][3][4][5]. Nowadays, most patients with clinically symptomatic lower limb atherosclerosis are treated with percutaneous transluminal angioplasty (PTA).…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that heat acclimation (HA) improves arterial elasticity [20], which has been shown to be directly linked to OxS [21] and inflammation [22]. However, there are no published reports about the impact of HA on OxS and inflammation induced by exhaustive exercise in the heat.…”
Section: Introductionmentioning
confidence: 99%